The military coup in Chile in 1973, the immediate reaction of international organisations, and the founding of the first rehabilitation program for torture victims in 1977 - Quiroga, José; Lira, Elizabeth (Torture Journal, 2022)
This paper documents the historical steps of the immediate reactions of the United Nations, Amnesty International, the World Council of Churches (WCC), the Inter-American Commission on Human Rights, and lawyers’ organisations in support of the victims of torture and others suffering gross violations of their human rights, as perpetrated by the Chilean military from 1973 to 1990. This article is also the history of the founding of the first rehabilitation programs for torture victims in Chile in 1977 and the other care programs for victims under local and international churches’ protection during the worst period of the military dictatorship. The actions of denunciation and defense of the victims were possible through national and international networks sustained in collaborative work from inside and outside Chile, which lasted for 17 years. The results and lessons learned projected the creation of new commissions, funds, and international networks that continue today in the international arena. The rehabilitation programs under the dictatorship began as a solidarity response to the needs of victims The rehabilitation programs, born during the dictatorship, projected their practice and experience to create a comprehensive health program as part of the State’s reparation measures. The testimonies of the victims made it possible to understand the consequences of human rights violations on individuals and society. State policies and civil society actions have sought to contribute to the reparation of victims through rehabilitation actions directly. This paper is part of the memory of that past by reconstructing the solidarity actions of denunciation and rehabilitation, and the details of which are often unknown.